2011
DOI: 10.1016/j.inhe.2011.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Integration of deworming into an existing immunisation and vitamin A supplementation campaign is a highly effective approach to maximise health benefits with minimal cost in Lao PDR

Abstract: Infection with soil-transmitted helminths (STHs) is a major public health problem in many developing countries; pregnant women and children are particularly at risk. Preventive chemotherapy (PC) -the intervention currently recommended by the World Health Organization (WHO) against the main helminth infections, including those caused by STHs -aims at reducing morbidity through periodical administration of anthelminthic drugs either alone or in combination.The Expanded Programme on Immunization (EPI) is one of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 6 publications
1
17
0
Order By: Relevance
“…Seven studies were found to have medium [ 16 , 17 , 19 23 ] and only four high [ 24 27 ] applicability for the use in economic evaluations. It should be noted that the more in-depth costing studies [ 24 27 ] – which also collected economic costs – reported notably higher MDA delivery costs (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven studies were found to have medium [ 16 , 17 , 19 23 ] and only four high [ 24 27 ] applicability for the use in economic evaluations. It should be noted that the more in-depth costing studies [ 24 27 ] – which also collected economic costs – reported notably higher MDA delivery costs (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The three studies identified for programmes targeting only Pre-SAC integrated their distribution either into Child Health Days [ 22 , 28 ] or used mobile teams [ 29 ]. Two studies were identified that investigated the cost of treating women of reproductive age within existing immunisation and vitamin A or iron supplementation campaigns [ 19 , 30 ]. These studies either integrated their distribution into Child Health Days (also targeting Pre-SAC) [ 19 ] or used village health workers [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Baseline MDA scenarios assumed the use of albendazole (with an economic cost of $0.50 per treated child in school-based programs[14, 32-35]) and a coverage rate of 56.2% of school-aged children, following the current reported rate in Brazil[36]. The baseline vaccination scenario assumed the criteria described in the human hookworm vaccine's target product profile (TPP)[37].…”
Section: Methodsmentioning
confidence: 99%
“…However, they could give an indication of cost savings associated with the integration of mass treatment against NTDs within existing immunization campaigns. [14]…”
Section: Discussionmentioning
confidence: 99%